Gender Differences in Multidimensional Mathematics Attitudes Among Junior Secondary Students: A Cross-Sectional Survey in the Indonesian Context - Talenta Valentina Christi; Hendra Kartika; Ramlah Ramlah (Program Studi Pendidikan Matematika, Universitas Majalengka, 2026)
Mathematics attitudes play a critical role in shaping students’ engagement, achievement, and long-term participation in STEM-related pathways. This study aimed to examine gender differences across four dimensions of mathematics attitudes—self-perceptions, value of mathematics, enjoyment, and perceived mathematics achievement—among junior secondary students in Indonesia. A quantitative cross-sectional survey design was employed involving 60 seventh-grade students (30 male and 30 female) selected through convenience sampling. Data were collected using an adapted version of the Attitudes Toward Mathematics Scale for Indonesian Students (ATMSE), comprising 26 items measured on a four-point Likert scale. Descriptive statistics based on median values were used to analyze gender-based patterns across dimensions. The findings indicate that both male and female students exhibit moderate, but not strongly positive, attitudes toward mathematics. Self-perceptions and enjoyment were generally situational and cautious, while perceived achievement emerged as the weakest dimension, with consistently low-to-moderate median scores across genders. Gender differences were minimal and largely descriptive rather than substantial, suggesting convergent attitudinal tendencies within this context. The results highlight a potential discrepancy between students’ classroom participation and the internalization of a confident mathematics identity. Strengthening students’ academic self-concept, reinforcing authentic recognition of achievement, and connecting mathematical learning to meaningful future pathways are recommended as strategic directions for pedagogical intervention. Future research employing inferential and longitudinal designs is needed to examine how these attitudinal profiles evolve and influence sustained engagement in mathematics and STEM trajectories